2020
DOI: 10.1002/pri.1858
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to key domains in low back pain guidelines: A cross‐sectional study of Danish physiotherapists

Abstract: Objective: The aim of the study was threefold: Firstly, to investigate the adherence to clinical practice guidelines for low back pain (LBP) among Danish physiotherapists with regard to three key domains: (a) activity, (b) work and (c) psychosocial risk factors. Secondly, to investigate whether adherence differed between physiotherapists working in private clinics (private physiotherapists) and physiotherapists working at public healthcare centres (public physiotherapists). Thirdly, to describe the physiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…The overall high guideline adherence in the treatment section ( n = 973, 72 %) observed in our study was also found in a recent study of Danish physical therapists [ 29 ], where the vast majority of participants was strictly or partly in line with the CPG. In contrast to these results, de Souza et al [ 30 ] stated that among Brazilian physical therapists, only 5–24 % showed full LBP guideline adherence.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall high guideline adherence in the treatment section ( n = 973, 72 %) observed in our study was also found in a recent study of Danish physical therapists [ 29 ], where the vast majority of participants was strictly or partly in line with the CPG. In contrast to these results, de Souza et al [ 30 ] stated that among Brazilian physical therapists, only 5–24 % showed full LBP guideline adherence.…”
Section: Discussionsupporting
confidence: 88%
“…Differences in reported guideline-adherent behaviour appear to be dependent upon several factors, including study design and the definition of guideline adherence. Husted et al [ 29 ], de Souza et al [ 30 ] and Ladeira et al [ 31 ] evaluated guideline adherence using clinical vignettes. In contrast, participants of the current study ranked their application frequency of treatment modalities as recommended in the NVL and guideline adherence was determined using a scoring system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate of guideline adherence is often low and varies widely [2][3][4]. Several barriers to guideline adherence have been identified, ranging from factors affecting individual physicians' knowledge about and attitude towards a certain guideline to external barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Within this model, management should include measures of possibly modifiable contributing factors like pain self‐efficacy, depression, anxiety, sleep quality, social functioning and work absenteeism (Tagliaferri et al., 2020). However, integration of the psychosocial domain in low back pain physiotherapy management is not optimal (Husted et al., 2020; Schaumberg, 2020). Physiotherapists have reported a lack of confidence to apply psychosocial strategies in their practice (Driver, Lovell, & Oprescu, 2019) and barely include psychosocially oriented illness perceptions in history taking (Roussel et al., 2016).…”
Section: Introductionmentioning
confidence: 99%